Identification of a RAD52 Inhibitor Inducing Synthetic Lethality in BRCA2-Deficient Cancer Cells - Yang, Qianye; Li, Yu; Sun, Rong; Li, Jian (Frontiers in Pharmacology, 2021)
The breast cancer susceptibility gene 1/2 (BRCA1/2) is frequently mutated in many malignant tumors, such as breast cancer and ovarian cancer. Studies have demonstrated that inhibition of RAD52 gene function in BRCA2-deficient cancer causes synthetic lethality, suggesting a potential application of RAD52 in cancer-targeted therapy. In this study, we have performed a virtual screening by targeting the self-association domain (residues 85–159) of RAD52 with a library of 66,608 compounds and found one compound, C791-0064, that specifically inhibited the proliferation of BRCA2-deficient cancer cells. Our biochemical and cell-based experimental data suggested that C791-0064 specifically bound to RAD52 and disrupted the single-strand annealing activity of RAD52. Taken together, C791-0064 is a promising leading compound worthy of further exploitation in the context of BRCA-deficient targeted cancer therapy.